Experimental Study on the Failure Mechanism of Tunnel Surrounding Rock under Different Groundwater Seepage Paths - Yingchao Wang; Yang Liu; Yongliang Li; Wen Jiang; Yueming Wang (Geofluids)
The influence of groundwater on tunnel engineering is very complicated. Due to the complexity of water flow water pressure transfer and uncertain defects in the stratum, all of which are key factors with regard to the design of tunnel engineering. Therefore, the variation of surrounding rock during excavation and the deformation and failure of soft surrounding rock under different seepage paths of underground water after excavation systematically. Experimental results showed that the stress change of surrounding rock caused by tunnel excavation can be divided into 3 stages: stress redistribution, stress adjustment, and stress rebalancing. In the process of water pressure loading, water flow rate is closely related to the experimental phenomenon. The between stable loading water pressure pore water pressure of the tunnel surrounding rock and the distance from the measuring point to the edge of the tunnel obey the exponential function of the decreasing growth gradient. With the increase of loading pressure, the pore water pressure and stress at the top of the tunnel increase, and the coupling of stress field and seepage field on both sides of surrounding rock more and more intense. The failure process of the tunnel can be divided into 6 stages according to the damage degree. The final failure pattern of the surrounding rock of the tunnel is mainly determined by the disturbed area of excavation. The arched failure area and the collapse-through failure area are composed of three regions. The surrounding rock is characterized by a dynamic pressure arch in the process of seepage failure, but it is more prone to collapse failure at low water pressure. The results of this study are the progressive failure mechanism of tunnel under different groundwater seepage paths and would be of great significance to the prevention of long-range disasters.